A Baseline Microbial Stability Study of Panchavalkaladi Taila and Dashamoola Taila-An Ayurvedic Formulation for Pelvic Inflammatory Disease - Matangee Pandya; Meera Cholera (AYUSHDHARA, 2022)
Pelvic inflammatory disease is an upper genital tract infection and inflammation. Panchavalkaladi Taila and Dashamoola Taila is having anti-inflammatory and analgesic property. Aim and Objectives: Present study was carried out for stability study of Panchavalkaladi Taila and Dashamoola Taila with respect to microbial diagnostic procedure. Materials and Methods: Sample of Panchavalkaladi Taila and Dashamoola Taila were prepared and studied at regular time intervals from the date of the preparation to the date of completion of clinic study to analysis mycological findings by Wet mount preparation and presence of bacteriological findings by Gram stain test. Result: Both samples were subjected to the microbiological study from date of preparation to the date of completion of clinical study. No any contaminations were found in microbiological study in both samples. Discussion and Conclusion: The baseline microbial profile was studied at regular interval of one month for total 15 month (between October 2020 to January 2022). At the end of every month study, samples were not showed presence of any microbes even in different temperature and humidity of this sea sore region. Conclusion: Obtained data of Panchavalkaladi Taila and Dashamoola Taila were concluded that both samples were showed good shelf life.